2016
DOI: 10.14295/cs.v7i1.439
|View full text |Cite
|
Sign up to set email alerts
|

Resistência do solo à penetração em sistemas de preparo e velocidades de deslocamento do trator

Abstract: The continuous use of tillage equipment without variation of the work depth can lead to soil compression problems. This study aimed to evaluate the spatial variability of soil resistance to penetration (RP) in a yellow ultisol profile in different tillage systems and tractor-equipment speeds. The experiment was carried out at the Agricultural Sciences Campus – UNIVASF, Petrolina- PE, Brazil, in randomized blocks with split plot with four repetitions. The treatments consisted of five tillage systems applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
5
0
7
Order By: Relevance
“…From the semivariogram analysis for RP (Table 4) we observed the adjustment of the spherical model for the evaluated layers and for the analysis of the maximum resistances and the occurrence depths of maximum resistances throughout the evaluated area, agreeing with Cortez et al (2014) when analyzing RP in Yellow Argisol under different intensities of tractor traffic. Similarly, Marasca et al (2011), Oliveira Filho et al, (2015 and Nagahama et al (2016) when evaluating spatial variability of RP verified a greater adjustment of the spherical model for soil physical attributes. It is observed that the nugget effect presented zero value for all the attributes in the studied layers.…”
Section: Layer (M)mentioning
confidence: 76%
See 2 more Smart Citations
“…From the semivariogram analysis for RP (Table 4) we observed the adjustment of the spherical model for the evaluated layers and for the analysis of the maximum resistances and the occurrence depths of maximum resistances throughout the evaluated area, agreeing with Cortez et al (2014) when analyzing RP in Yellow Argisol under different intensities of tractor traffic. Similarly, Marasca et al (2011), Oliveira Filho et al, (2015 and Nagahama et al (2016) when evaluating spatial variability of RP verified a greater adjustment of the spherical model for soil physical attributes. It is observed that the nugget effect presented zero value for all the attributes in the studied layers.…”
Section: Layer (M)mentioning
confidence: 76%
“…It is observed that the nugget effect presented zero value for all the attributes in the studied layers. Values of nugget effect close to zero were found by Bottega et al (2013) and Nagahama et al (2016) who pointed out that the occurrence of such values increases the accuracy of estimates through kriging. This is because the lower the proportion of the nugget effect in relation to the variogram baseline, the greater the continuity of the phenomenon and the variance of the estimate, and the greater the confidence that can be had in the estimation (Bottega et al, 2013).…”
Section: Layer (M)mentioning
confidence: 85%
See 1 more Smart Citation
“…Os semivariogramas foram ajustados e a partir deles foram selecionados modelos com base no melhor coeficiente de determinação (r 2 ) e na menor soma de quadrados do resíduo, sendo testados os modelos esférico, exponencial, gaussiano, linear, linear sem patamar e efeito pepita puro. Nos semivariogramas ajustados, foram definidos os seguintes parâmetros: efeito pepita (C0); patamar (C0 + C1) e alcance (A) (Marasca et al, 2011;Bottega et al, 2011;Bottega et al, 2013;Nagahama et al, 2016).…”
Section: Methodsunclassified
“…Houve diferença entre as áreas para Pt e Ds na camada de 0,20--0,40 m de solo de Casa Nova e nas camadas superficiais do solo de Sento Sé, em ambas com ocorrência de redução de Ds e aumento de Pt no solo com uso agrícola em relação à com caatinga, o que demonstra relação estreita e inversa entre os atributos (Cortez et al, 2011). Contudo, esses resultados aparentemente não têm relação com o manejo do solo utilizado nas áreas, visto que tais atributos em solos arenosos do semiárido parecem não ser afetados pela ação das ferramentas de preparo e tráfego de máquinas agrícola (Cortez et al, 2011;Nagahama et al, 2016), mas sim pelas características dos solos da região (Arcoverde et al, 2015).…”
Section: Comparação De Médias Dos Dados Dos Atributos Físicos Do Solounclassified